Intermittent Stream Application Under Border Irrigation - Awasthi, M.K.; Sharma, Y.K.; Pandey, R.N. (Journal of Soil and Water Conservation, 2022)
The continuous application of stream from head of border have been an irrigation practice since long. The intermittent application in border irrigation is useful in saving time and water. An experiment was conducted to know the effect of slope ,stream size and number of water application, on distance covered by water front, time of front travel and volume of water consumption. Increasing slopes from 0.3 to 0.6% water front travel time from reduced 33.15 min to 26.84 min, and volume of water from 1.85 cu.m. to 1.46 cu.m. The intermittent application significantly influenced the time and water consumption by reducing time from 32.02 min to 28.6 min and water consumption from 1.77 cu.m. to 1.58 cu.m. Similarly, increasing discharge rate from 0.5 1ps per m width of border to 1.71ps per in width of border significantly decreased the time consumption. An mathematical equation was also developed to predict the time consumption by waterfront advance under different slopes, number of spells and discharge rate.